Parents' perception of health‐related quality of life in children and adolescents with excess weight - Melissa Maria Romero Nascimento; Tatiana Rocha Melo; Rogério Melo Costa Pinto; Nívea Macedo Oliveira Morales; Tânia Maria Silva Mendonça; Helena Borges Martins da Silva Paro; Carlos Henrique Martins Silva (Brazilian Society of Pediatrics, 2016)
Objective: To evaluate the perception of parents or caregivers on the health‐related quality of life (HRQOL) of children/adolescents with overweight/obesity and possible factors associated with this perception. Methods: This was a cross‐sectional study involving 297 caregivers of children and adolescents with normal weight (n = 170) and with overweight/obesity (n = 127), from public and private schools in the study municipality. HRQOL scores obtained through the Child Health Questionnaire ‐ Parent Form 50 (CHQ‐PF50) were compared according to the nutritional status and gender of the children/adolescents. Multiple regression analysis was used to determine the predictive value of studied variables for the variation in HRQOL scores. Results: Parents of children/adolescents with overweight/obesity attributed lower HRQOL scores to their children in the following domains: physical functioning (p < 0.01; d = 0.49), self‐esteem (p < 0.01; d = 0.38), parental impact‐emotional (p < 0.05; d = 0.29), family cohesion (p < 0.05; d = 0.26), physical summary score (p < 0.05; d = 0.29), and psychosocial sum‐mary score (p < 0.05; d = 0.25). In the multiple regression models, the variables with the highest contribution to the variation in HRQOL scores were: in the physical functioning domain, parental impact‐time (β = 0.23; p < 0.05); self‐esteem, nutritional status (β = −0.18; p ≤ 0.01); emotional impact on parents, impact on parents' time (β = 0.31; p < 0.05); and in family cohesion, global behavior (β = 0.30; p < 0.05). Conclusions: A negative impact on HRQOL of children/adolescents with overweight/obesity was observed in the physical and psychosocial aspects. The nutritional status was the variable with the greatest contribution for the assessment the self‐esteem of children and adolescents in this study.